Improving the efficiency of high octane gasolines manufacturing; Chemical Reactors (CHEMREACTOR-22) - Dolganov I. M. Igor Mikhailovich; Ivanchina E. D. Emilia Dmitrievna; Chuzlov V. A. Vyacheslav Alekseevich; Dolganova I. O. Irena Olegovna (2016, 2016)
Title screen